Phenolic Compounds and Antioxidant Activity of Rice–Tartary Buckwheat Composite as Affected by In Vitro Digestion - Nuo Li; Guifang Zhang; Dongjie Zhang (Journal of Chemistry)
The present study aimed to evaluate the phenolic compounds and antioxidant activity of rice–tartary buckwheat composite (RTBC) as affected by in vitro digestion to explore the structure-activity relationship of the release of total phenolic content (TPC) and total flavonoid content (TFC) with the antioxidant activity of RTBC during in vitro oral, gastric, and intestinal digestion stages. The release of TPC and TFC from RTBC increased significantly after in vitro digestion (P<0.05), and the change of antioxidant activity was consistent with that of TPC and TFC. Compared with the initial stage of digestion, the antioxidant activity of RTBC was increased after digestion (P<0.05), and there was a strong correlation between antioxidant activity and the release of TPC and TFC (0.954 < R < 0.997; P<0.05). The phenolic compounds released in the oral, gastric, and intestinal digestion stages varied, and eight phenolic compounds were identified by UPLC-Triple-TOF/MS, namely, quercetin-3-O-robinoside-7-O-sophoroside, quercetin-3-O-neohesperidoside-7-O-glucoside, forsythobiflavone A, forsythobiflavone B, quercetin-3-O-rutinoside-7-O-glucoside, rutin, isoquercetin, and ferulic acid. These results indicated that in vitro digestion significantly increases the release of phenolic compounds and flavonoids from RTBC and there is a higher antioxidant activity after digestion than before digestion. The phenolic compounds released after digestion of RTBC are beneficial to health protection.